Exploring FinTech trends in Jordan: insights from the post-COVID-19 era - Al-Okaily, M.; Al-Qudah, A.A.; Alkhwaldi, A.F.; Alkhatib, A.W.; Al-Okaily, A.; Abu Salih, Bilal (2025)
Purpose: This study aims to investigate how the COVID-19 pandemic has impacted the growth of FinTech within the Jordanian context. Specifically, it examines the antecedent factors influencing users’ intentions to adopt and use FinTech services during this unprecedented period. Design/methodology/approach: A quantitative research method approach with partial least squares-structural equation modelling was used to test the research proposed model. Findings: The results of the structural path revealed that the drivers of behavioural intentions to use FinTech services are perceived usefulness, perceived self-efficacy, perceived vulnerability, subjective norms, perceived severity, perceived certainty and resistance to use and these factors explain 79.5% of the variance of behavioural intention. Research limitations/implications: This study identifies key factors for FinTech acceptance in Jordan, offering actionable insights for policymakers and service providers. Building user trust in service and technology (security, effectiveness and transparency) is crucial, alongside leveraging social influence (testimonials, endorsements) and boosting awareness/knowledge through campaigns and educational initiatives. This study identifies key factors for FinTech acceptance in Jordan, offering actionable insights for policymakers and service providers. Building user trust in service and technology (security, effectiveness and transparency) is crucial, alongside leveraging social influence (testimonials, endorsements) and boosting awareness/knowledge through campaigns and educational initiatives. This study’s generalizability is limited by its sample, drawn from three Jordanian regions and dominated by potential users. Comparing actual and potential user perceptions, alongside including users from diverse contexts (e.g. other developing countries), could address this. In addition, using qualitative methods alongside the quantitative approach and exploring indirect relationships (mediating/moderating) would provide richer insights into FinTech acceptance in Jordan. Originality/value: While prior research has explored FinTech adoption, including studies conducted in Jordan, this study makes several key contributions. Firstly, it specifically examines FinTech trends within the post-COVID-19 era in Jordan, a period marked by accelerated digital transformation and evolving user behaviours. Secondly, it extends existing models of FinTech adoption by incorporating “perceived self-efficacy, perceived vulnerability, subjective norms, perceived privacy, perceived severity, perceived value, perceived certainty and resistance to use”, in addition to the established factors of “perceived usefulness and ease of use”. This expanded model provides a more holistic understanding of the drivers and barriers to FinTech adoption in this context. Finally, this research provides empirical evidence from the Jordanian market, offering valuable insights for financial institutions and policymakers seeking to promote FinTech adoption and financial inclusion in a developing economy undergoing rapid digital change. This focus on the post-pandemic Jordanian context, combined with the extended theoretical model, offers a novel contribution to the literature.